The King of Tars - Chandler, John H., 1974- (Book collections on Project MUSE., 2015)
"The King of Tars is an early fourteenth-century Middle English poem, a variation on the Constance- tale, celebrating the marriage of a Christian princess to a Muslim sultan and the sultan's conversion to Christianity."--